If 1 is a zero of polynomial ax-3(a-1) x-1 and then find the value of a
Answers
Answered by
0
Putting value of x=1 in,
p(x)=ax-3(a-1)x-1
p(1)= a×1-3(a-1)×1-1
0 = a-3a+3-1
0 = -2a+2
2a=2
a = 2÷2
a=1
So, value of 'a' is 1 ...
p(x)=ax-3(a-1)x-1
p(1)= a×1-3(a-1)×1-1
0 = a-3a+3-1
0 = -2a+2
2a=2
a = 2÷2
a=1
So, value of 'a' is 1 ...
Answered by
0
heya it's Aastha......
p(1)= ax^2-3(a-1) x-1
p(1)= ax^2- 3ax+3x -1
p(1)= a - 3a + 3 -1
= -2a + 2
a = 1 .
I hope it help you
p(1)= ax^2-3(a-1) x-1
p(1)= ax^2- 3ax+3x -1
p(1)= a - 3a + 3 -1
= -2a + 2
a = 1 .
I hope it help you
Similar questions